QUALITY IMPROVEMENT Supporting a hospital in difficulty: experience of a ' buddying' agreement to implement a new medical pathway. Issue 1 (2019) - Leach, Richard; Banerjee, Sandip; Beer, Gail; Tencheva, Svetka; Conn, Deidre; Waterman, Ashley; Parrott, Jackie; Gifford, Julie; Steddon, Simon; Abbs, Ian; Pritchard, Amanda; Kerr, Ron; et al.
No abstract available